Effect Of Operation Strategies On The Economic Performance Of A Hybrid Photovoltaic-Micro Gas Turbine Trigeneration System - F., Basrawi; Hassan, Ibrahim; Chand, M. R. R.; Yamada, Takanobu (2014)
This study presents the economic performance of a photovoltaic (PV) and micro gas turbine trigeneration system (MGT-TGS) based hybrid energy system with various operation strategies. The hybrid system covers power, heating and cooling load of a selected building located in a tropical region. The core prime mover of each operation strategy is an MGT with power output capacity of 30kW or 65kW. An energy balance analysis was conducted and the economic performance of each operation strategy was analyzed using Life Cycle Cost Analysis. It was found that all operation strategies can only generate Net Profit when the electricity cost is not subsidized. Combination of photovoltaic and MGT-TGS with power-match operation strategy had the highest Net Profit and was the simplest hybrid system. This was mainly because this system did not require battery that has high cost. Thus, this is the most optimum operation strategy when economic performance is considered.